Vztah mezi vzdĕláním a prevalencí kardiovaskulárních rizikových faktorů - Bobák, M; Skodová, Z; Písa, Z (Casopis lekaru ceskych, 1994)
BACKGROUND: Although socioeconomic factors are significant predictors of cardiovascular disease risk, their role has not yet been fully elucidated in our country. The objective of the present work was to find out whether they participate, and to what extent, in cardiovascular diseases. METHODS AND RESULTS: We re-analyzed data assembled during the second cross-sectional survey of the MONICA project in 1988: the investigated population, comprising 1349 men and 1407 women, was divided into four age groups (25-34, 35-44, 45-54 and 55-64 years) and into three groups by the highest achieved education (elementary, secondary and university). The age specific prevalence of cigarette smoking, obesity (expressed as BMI), serum cholesterol and blood pressure reading by level of education was investigated. While in the younger age groups--consistent with observations in western countries--an inverse correlation between education and risk factors predominates, in the older age groups this relationship is reversed. The contrast between groups by attained education is manifested most markedly in smoking (men, trend p < 0.001), obesity (women, trend p < 0.001), total cholesterol (men, women, the difference is, however, not statistically significant), and systolic blood pressure in men (trend p < 0.001). In all these risk factors the profile is more favourable in subjects with a higher (university) education. An exception is the lower HDL cholesterol level (p < 0.001) in women with elementary education (in men a reversed relationship, but not statistically significant). The contrast between younger and older age groups was manifested most markedly in smoking and obesity. CONCLUSIONS: The observation supports the hypothesis that gradually a change of the socioeconomic gradient of cardiovascular diseases is taking place. The results indicate that subjects with lower education in the younger age groups and subjects with higher education in the older age groups are a population with an unfavourable risk profile on which preventive programmes should be focused in the first place.
Keywords: obezita; Cholesterol; kardiovaskulární nemoci; Humans; cholesterol; lidé středního věku; prevalence; Female; rizikové faktory; dospělí; lidé; Adult; ženské pohlaví; Cardiovascular Diseases; krevní tlak; Male; Middle Aged; Czech Republic; Cross-Sectional Studies; Prevalence; stupeň vzdělání; Obesity; Smoking; Česká republika; mužské pohlaví; kouření; Blood Pressure; průřezové studie; Educational Status; Risk Factors